1976
DOI: 10.1002/eji.1830061117
|View full text |Cite
|
Sign up to set email alerts
|

Differences in effect of isoproterenol stimulation on levels of cyclic AMP in human B and T lymphocytes

Abstract: The level of cyclic AMP (cAMP) in human lymphocytes in the presence or absence of isoproterenol stimulation was studied in various lymphocyte subpopulations containing different proportions of B and T lymphocytes. Lymphocytes from thymus and peripheral blood (which contain a majority of T cells) were more sensitive to isoproterenol action than lymphocytes from tonsils or adenoids (where B cells are predominant). Using purified B or T lymphocytes from peripheral blood, tonsils or adenoids, we observed an absenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
1

Year Published

1978
1978
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(10 citation statements)
references
References 18 publications
3
6
1
Order By: Relevance
“…These observations may further support the nonrandom nature of the distribution of receptors for autacoids on T cell subsets. The selectivity in the responsiveness of different populations of T cells to beta adrenergic agonists and histamine had earlier been reported (17)(18)(19). Corticosteroid resistant murine thymocytes were less responsive to isoproterenol than untreated thymocytes.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…These observations may further support the nonrandom nature of the distribution of receptors for autacoids on T cell subsets. The selectivity in the responsiveness of different populations of T cells to beta adrenergic agonists and histamine had earlier been reported (17)(18)(19). Corticosteroid resistant murine thymocytes were less responsive to isoproterenol than untreated thymocytes.…”
Section: Resultssupporting
confidence: 53%
“…The latter were more responsive than lymphoid cells from spleen, lymph node, and blood (17). Niaudet et al (19) reported that T lymphocytes isolated from human peripheral blood produced more cAMP in response to isoproterenol than T cells isolated from human tonsils and adenoids.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, mature corticosterone-resistant thymocytes were demonstrated to express ␤ -AR at levels equivalent to those seen in peripheral T cells [123,131] . Despite the differential level of expression on immature and mature thymocytes, the efficiency of ␤ -AR coupling to adenylate cyclase in unfractionated thymocytes and mature thymocytes was comparable to that seen in lymphocytes from spleen and lymph nodes [132] . Further, unfractionated thymocytes were shown to generate an isoproterenol-induced cAMP response that is equivalent to that in splenocytes, even though splenocytes express a far greater number of ␤ -ARs [133] .…”
Section: Expression Of Ars In the Thymusmentioning
confidence: 99%
“…Because it is difficult to study samples of lung in human subjects, several investigators have used either peripheral blood leukocytes or lymphocytes to show that asthmatics have decreased stimulation of cyclic AMP by beta adrenergic agonists (7,8). Two problems must be considered in assessing these studies: (a) beta adrenergic responses and receptors in T and B lymphocytes may be quite different (9,10), and thus changes in adrenergic response in asthmatics might reflect altered distribution of cells in lymphocyte subpopulations; and (b) prior administration of beta adrenergic agonists reportedly diminishes subsequent beta adrenergic stimulation of leukocyte cyclic AMP (11)(12)(13). Thus, changes in responsiveness of asthmatics might arise from therapy as well as from the disease itself.…”
Section: Introductionmentioning
confidence: 99%